The melting performance of high alumina blast furnace slags (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
With a view to understanding the performance of the blast furnace slag with high Al2O3 content, the effects of slag compositions (w(MgO)/w(Al2O3), w(CaO)/w(SiO2), and w(Al2O3)) on the melting performance (melting characteristic temperature and melting heat) of blast furnace slag with high Al2O3 content were investigated by the differential scanning calorimeter (DSC) method. The melting end temperature (Tend) for almost all the slags has no obvious change with the increase of w(MgO)/w(Al2O3). The experimental results indicate that increasing w(CaO)/w(SiO2) and w(Al2O3) of the slag will raise Tend of the blast furnace slag. Because the liquidus temperature of the slag moves toward elevated temperature due to the increasement of w(CaO)/w(SiO2) and w(Al2O3) based on the analysis of the phase diagram. The effects of compositions (w(MgO)/w(Al2O3), w(CaO)/w(SiO2), and w(Al2O3)) on the melting onset temperature (Tonset) of slag are complex, which is considered that some high melting point compounds are generated or eutectic reverse reactions appear when the slag compositions change. Higher w(MgO)/w(Al2O3) will lead to higher melting heat of the slag because higher w(MgO)/w(Al2O3) causes more CaO replaced by MgO and the lattice energy of MgO is higher than CaO lattice energy, which results in more energy required to destroy MgO lattice during the slag melting than that of CaO. In addition, more Al3+ replaces Si4+ in the slag to form [AlO4]5- tetrahedron with the increase of w(Al2O3) based on Raman spectra analysis, thus the depolymerization of the [AlO4]5- tetrahedron is required for more energy than that of [SiO4]4- tetrahedron, thus, the melting heat of the slag increases.
Keywords: High alumina blast furnace slag; Melting characteristic temperature; Melting heat; Differential scanning calorimetry; Raman spectrum analysis